2010
DOI: 10.1371/journal.pone.0012996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel p53 Pathway Activating Small-Molecule Compounds Reveals Unexpected Similarities with Known Therapeutic Agents

Abstract: Manipulation of the activity of the p53 tumor suppressor pathway has demonstrated potential benefit in preclinical mouse tumor models and has entered human clinical trials. We describe here an improved, extensive small-molecule chemical compound library screen for p53 pathway activation in a human cancer cell line devised to identify hits with potent antitumor activity. We uncover six novel small-molecule lead compounds, which activate p53 and repress the growth of human cancer cells. Two tested compounds supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 48 publications
4
108
0
1
Order By: Relevance
“…Another small molecule, BMH-21, was recently reported to target PolI activity through its ability to promote the proteasomal degradation of RPA194, the large catalytic subunit of PolI holocomplex [126]. Although BMH-21 intercalates into DNA with high affinity to GC-rich regions, it does not elicit a DNA damage response [127] and its ability to activate p53 is probably mediated by ribosome biogenesis stress. This promising agent was shown to effectively impede the growth of different cancer cells, both in vitro and in vivo [126].…”
Section: The Ribosome Biogenesis Machinery As a Putative Cancer Theramentioning
confidence: 99%
“…Another small molecule, BMH-21, was recently reported to target PolI activity through its ability to promote the proteasomal degradation of RPA194, the large catalytic subunit of PolI holocomplex [126]. Although BMH-21 intercalates into DNA with high affinity to GC-rich regions, it does not elicit a DNA damage response [127] and its ability to activate p53 is probably mediated by ribosome biogenesis stress. This promising agent was shown to effectively impede the growth of different cancer cells, both in vitro and in vivo [126].…”
Section: The Ribosome Biogenesis Machinery As a Putative Cancer Theramentioning
confidence: 99%
“…Interestingly, a recent chemical library screen lead to the discovery of several molecules which activate the p53 pathway and kill cancer cells via interference with the DNA topology [65]. One of the compounds, BMH-21, binds to GC-rich sequences, in particular in ribosomal DNA genes, leading to the inhibition of RNA Pol I via proteasome-dependent degradation of Pol I subunit RPA194 and segregation of nucleolar proteins [66].…”
Section: Compounds Affecting Upstream Regulators Of Mdm2/xmentioning
confidence: 99%
“…Lead molecules arising from large unbiased screens have a diversity of action mechanisms including inhibition of sirtuins, and regulation of p53 folding and binding (1, 2). We conducted a cell-based high-throughput imaging screen to identify small molecule p53-activators and discovered and validated six lead compounds as activators of p53 based on their ability to stabilize p53, activate p53 reporter and p53 target genes and transcriptional profiling consistent with p53 responses (8). Characterization of their mechanism of p53 activation revealed that two of the compounds caused DNA-damage and mediated p53 stabilization through activation of ATM-signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The present study focused on characterization of the mechanism of action of compounds BMH-9, BMH-22 and BMH-23 arising from our initial high-throughput screen for p53 activators (8). We show here that these compounds function as Pol I inhibitors and similarly to BMH-21, cause proteasome-dependent degradation of RPA194.…”
Section: Introductionmentioning
confidence: 99%